Z teorii i praktyki edukacji plastycznej na poziomie kształcenia wczesnoszkolnego, czyli o działaniach edukacyjnych oraz udziale technik i mediów plastycznych w stymulowaniu dziecięcej kreatywności i wyobraźni plastycznej – wymiar poznawczy - Mazepa-Domagała, Beata (Chowanna, 2019)
The present text is an effect of considerations devoted to art education of an early-school child focused on stimulating children’s creativity and artistic imagination. The first part of the article presents considerations regarding the issue of artistic imagination and creativity. The second part discusses the concept of designing artistic activities at the level of early school education as a stimulator of imagination and child creativity. The third part of the article is an attempt to present the possibilities of using the techniques of contemporary art as a platform for pedagogical activities.